A RESEARCH REVIEW OF THE INTER-FAITH HARMONY AMONG VARIOUS RELIGIOUS SCHOOLS OF THOUGHT IN PAKISTAN - Dr. Abdul Rehman Khan; Dr. Syed Mehmood Ahmad Hasnain; Dr. Usma Anser; Dr. Asghar Ali (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
There are three main religious schools of thought existing in Pakistan, which are Hanafi Fiqh, Ahl-ul Hadith, and Shias. How to create Inter-faith harmony between these religious schools of thought are briefly discussed in this article. No doubt, there are different opinion among the religious schools of thought. But difference of opinion among the Jurists, it is proved, is based on rules existing since the very initial stages of the evolution of Fiqh. This difference of opinion reflects the beauty of the Islamic Shariah, the depth of the Islamic Fiqh and the compatibility of the Islamic Shariah with the demands of changing eras. Most of the differences are related to minor details _ not the fundamentals _ mostly reflecting what is better and what not. Most of the fundamentals are unanimously agreed upon. In the present age, we should focus on the agreed upon teachings and to preach them, and in case of controversies, we should respect our opponents and be broad-minded. So far as the approach of schools of Fiqh existing in Pakistan towards constitution and legislation are concerned, there is no fundamental difference between the Hanafi Fiqh and Ahl-ul Hadith. But there is some difference with the Shias. However, this difference has never been a hindrance to the Islamization of laws in the country. We find some examples of this phenomenon in the classical jurists as well.